(Tables 1-2) Re, Os concentrations and 187Os/188Os of gabbros from ODP Site 118-735B - Blusztajn, Jerzy S; Hart, Stanley R; Ravizza, Gregory E; Dick, Henry J B (Supplement to: Blusztajn, JS et al. (2000): Platinum-group elements and Os isotopic characteristics of the lower oceanic crust. Chemical Geology, 168(1-2), 113-122, https://doi.org/10.1016/S0009-2541(00)00186-8, 2000)
We present osmium isotopic compositions and Os, Re and platinum-group element (PGE) contents in the lower oceanic crust gabbros from ODP Site 735B on the Southwest Indian Ridge. The average gabbros are very depleted in PGEs, e.g. the Os concentrations are very low and range from 0.5 to 38 ppt. One troctolite sample is an exception, containing, e.g. 376 ppt Os, 396 ppt Ir and 8 ppb Pd. Re contents are extremely heterogeneous, ranging from 128 ppt to 28 ppb. The present day 187Os/188Os varies from 0.140 to 0.467, and correlates with Rb/Cs, suggesting that seawater alteration affected the Os isotopic system. The average Os content in the lower oceanic crust is about 9 ppt while median value for Re is about 487 ppt. Such very high Re/Os is relatively similar to the upper MORB-type oceanic crust, indicating that recycled ocean crust basalts and gabbros will rapidly develop very radiogenic Os isotopic signatures.